2009
DOI: 10.1107/s0108768109046060
|View full text |Cite
|
Sign up to set email alerts
|

How to easily replace the independent atom model – the example of bergenin, a potential anti-HIV agent of traditional Asian medicine

Abstract: Bergenin, which has been isolated from a variety of tropical plants, has several pharmacological applications in traditional Asian medicine. Its electron-density distribution was obtained from a room-temperature low-resolution X-ray data set measured with point detection making use of multipole populations from the invariom library. Two refinement models were considered. In a first step, positional parameters and ADPs were refined with fixed library multipoles (model E1). This model was suitable to be input in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
(41 reference statements)
3
36
0
Order By: Relevance
“…These dependencies are being applied in the analysis of experimental electron densities or electron densities built from crystal structure data [6], sometimes to interactions other than the hydrogen bond [7], as well as in the analysis of theoretical calculations in solid state [8]. However, there is few information about the applicability domain and accuracy of these dependencies when used as estimators of HB energies.…”
Section: Introductionmentioning
confidence: 99%
“…These dependencies are being applied in the analysis of experimental electron densities or electron densities built from crystal structure data [6], sometimes to interactions other than the hydrogen bond [7], as well as in the analysis of theoretical calculations in solid state [8]. However, there is few information about the applicability domain and accuracy of these dependencies when used as estimators of HB energies.…”
Section: Introductionmentioning
confidence: 99%
“…Among other options, transferred multipolar models were developed, one of them being based on a recently introduced concept of invarioms 2. They were devised to replace an independent atom model (IAM)3, 4 by using database entries of multipolar parameters obtained within the Hansen–Coppens aspherical‐atom formalism5 from X‐ray measurements of high quality6 or from quantum chemical calculations 2. 7 As well as taking as less time than IAM to employ,8, 9 their use allows reaching the accuracy of conventional multipole refinement against high‐resolution data 8.…”
Section: Introductionmentioning
confidence: 99%
“…Having gained the popularity in the last decade, the invariom approach has already been successfully applied for describing different organic systems and helping with different chemical problems inaccessible by full experimental multipole refinement. Those include a more reliable absolute structure determination for light‐atom compounds,13 charge density studies from low (normal) resolution datasets,9, 14, 15 only collectible with copper radiation,4 and of larger molecules with poor reflective power,16 identification and treatment of a disorder,17 and so on. Thus, being an extremely promising approach, it can even use other starting geometries than from X‐ray diffraction, for example, those obtained from quantum chemistry or NMR spectroscopy 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, an ED can be provided from conventional x-ray diffraction data. Moreover, it was shown that ED properties obtained from an invariom application to a conventional x-ray data set were comparable to the corresponding results from a high-resolution multipole refinement [8,9].…”
Section: Discussionmentioning
confidence: 50%